Concerted electron-nuclear motion in proton-coupled electron transfer-driven grotthuss-type proton translocation - Arsenault, Eric A. (2022)
Photoinduced proton-coupled electron transfer and long-range two-proton transport via a Grotthuss-type mechanism are investigated in a biomimetic construct. The ultrafast, nonequilibrium dynamics are assessed via two-dimensional electronic vibrational spectroscopy, in concert with electrochemical and computational techniques. A low-frequency mode is identified experimentally and found to promote double proton and electron transfer, supported by recent theoretical simulations of a similar but abbreviated (non-photoactive) system. Excitation frequency peak evolution and center line slope dynamics show direct evidence of strongly coupled nuclear and electronic degrees of freedom, from which we can conclude that the double proton and electron transfer processes are concerted (up to an uncertainty of 24 fs). The nonequilibrium pathway from the photoexcited Franck-Condon region to the E2PT state is characterized by an ∼110 fs time scale. This study and the tools presented herein constitute a new window into hot charge transfer processes involving an electron and multiple protons.